2015
DOI: 10.11604/pamj.2015.21.59.5688
|View full text |Cite
|
Sign up to set email alerts
|

Les carcinomes de la thyroïde: profils épidémiologique, clinique et thérapeutique, à propos de 102 cas

Abstract: Les carcinomes thyroïdiens sont des tumeurs malignes assez rares, représentant 1% des cancers. Ils sont généralement de bon pronostic, et présentent des aspects cliniques et évolutifs variés selon leur origine histologique. Notre travail est une étude rétrospective portant sur 102 cas de carcinomes de la thyroïde, colligés sur un nombre total de 811 gestes chirurgicaux thyroïdiens, au service d'oto-rhino-laryngologie et de chirurgie cervico-faciale de l'hôpital militaire Avicenne de Marrakech, sur une période … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…PTC was the most common histological subtype. These results are consistent with those of African and world series, 8–12 and with those of the Tunisian registry of cancers that reported a mean age of 47.4 years in men and 46.0 years in women. A Tunisian study of 318 differentiated thyroid carcinomas, 14 reported a female predominance of 87.73% and a sex ratio M/F of 0.13.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…PTC was the most common histological subtype. These results are consistent with those of African and world series, 8–12 and with those of the Tunisian registry of cancers that reported a mean age of 47.4 years in men and 46.0 years in women. A Tunisian study of 318 differentiated thyroid carcinomas, 14 reported a female predominance of 87.73% and a sex ratio M/F of 0.13.…”
Section: Discussionsupporting
confidence: 92%
“…PTMC accounted for 37.5% of total cases and 42.1% of PTCs. Similar results were reported in the literature 10,12,17,18 . The increase in the incidence and the rate of PTMC is related to the improvement of diagnostic means (cervical ultrasound and fine needle aspiration) allowing the detection of these tumors at a subclinical stage.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Five to ten percent of thyroid nodules are malignant[ 3 - 6 ]. Thyroid cancer only represents 1% of all cancers worldwide[ 7 , 8 ] but has occupied the fifth position among all cancers in France and Canada in women in terms of incidence and twentieth in terms of mortality in 2005[ 9 - 11 ]. The improvement of diagnostic techniques by means of thyroid ultrasound, fine needle aspiration, Computed Tomography scan and detailed histopathological analyses partly explains the increase in incidence of thyroid cancer[ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Papillary microcarcinoma of the thyroid have a rather strict histological definition demarcated by the World Health Organization in 1988 as cancers having a diameter equal or inferior to 10 mm in the anatomopathological examination [1]. They established, then, that microcarcinomas constitute about 30% of all papillary carcinomas and about 40% in 2003, making it the most common variant of papillary carcinoma in the United States.…”
Section: Introductionmentioning
confidence: 99%